Proposta de modelo de a????es educativas para idosos em educa????o a dist??ncia (Ead) na for??a a??rea brasileira - Rissi, Luciane Cristina (2020)
The phenomenon of population aging in the last 50 years has been demanding solutions from the society to the proliferation of healthy habits and elderly people quality of life, especially regarding social inclusion and its connection with the community in which they are inserted. The present project seeks, through distance health education, to present a model of inclusion of the elderly in society. Therefore, it proposes to answer the following question: ???What are the critical success factors in the construction of a management model in distance education that can contribute to the health of the elderly public of the Brazilian Air Force????. The methodology used for this research will be based on the qualitative cross-sectional case study method, having as a research unit in S??o Paulo Air Force Hospital Elderly Group. For the results, this project highlights the use of distance education, in the problem-solving process throughout the development and/or improvement of specific skills for the elderly and as a contribution to a healthy aging, the success factors include tasks orientation, motivation sources, teacher???s role and cultural sensitivity. As a practical contribution, the study aims to outline the distance education project for the elderly within the scope of health in S??o Paulo Air Force.